Physiological Correlates of Fluent and Stuttered Speech Production in Preschool Children Who Stutter - Walsh, Bridget (J Speech Lang Hear Res, 2019)
PURPOSE: The purpose of this study was to compare physiological indices of sympathetic nervous system arousal recorded during fluent and stuttered utterances in a preschool children who stutter (CWS). METHOD: Twenty-two 4- to 5-year-old CWS participated in the experiment. We recorded children's skin conductance response amplitude and frequency, blood pulse volume amplitude, and pulse rate as they completed a picture description task. We then compared indices of phasic sympathetic arousal recorded during stuttered versus fluent utterances. In addition, children's communication attitudes were evaluated with a self-report measure. RESULTS: We detected significantly higher sympathetic arousal during stuttered utterances compared to fluent utterances. Specifically, we found larger skin conductance responses occurring at an increased frequency and decreased blood pulse volume amplitudes during stuttered speech. The behavioral measure indicated a negative communication attitude in only one-third of the participants. CONCLUSION: Our findings suggest that preschool CWS may exhibit higher levels of sympathetic arousal during stuttered speech compared to when they are speaking fluently. We discuss the potential impact of increased sympathetic arousal on speech regulatory mechanisms in early childhood stuttering and present questions to guide future research.